The relationship between adolescents' materialism and cooperative propensity: The mediating role of greed and the moderating role of awe. (April 2022) - Wu, Qin; Zhang, Yuxuan; He, Wen; Cui, Liying
Abstract: Adolescence is an important period in regard to personal values and social development. As a value orientation that emphasizes wealth and interests and pursues "external goals", it is unclear whether and how the materialistic values of adolescence affect adolescents' social interaction, specifically, their propensity to cooperate. This study selected four middle schools in Shanghai, China, for testing using a convenience sampling method; 557 students (mean age = 14.56 years) completed questionnaires that measured materialism, cooperative propensity, greed, and awe. The results showed that adolescent materialism does not directly affect cooperative propensity, but propensity to cooperate can be indirectly influenced through the mediating effect of greed. Further, the mediation effect was moderated by awe; specifically, compared to adolescents who score low for awe traits, the mediating role of greed does not exist for adolescents who score high for awe traits. This finding suggests that awe can act as a buffer against the negative effect of greed on cooperative propensity, which can provide practical guidance for cultivating the cooperation of adolescents.